2020
DOI: 10.21203/rs.3.rs-59509/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Clinical profiles, Outcomes and Risk Factors among Type 2 Diabetic Inpatients with Diabetic Ketoacidosis and Hyperglycemic Hyperosmolar State: A Hospital-Based Analysis over a 6-Year Period

Abstract: Objective:Diabetic ketoacidosis (DKA) and hyperosmolar hyperglycemic state (HHS) are the two most common hyperglycemic emergencies (HEs) associated with diabetes mellitus. Individuals with HEs can present with combined features of DKA and HHS. The objective of this study is to assess the clinical characteristics, therapeutic outcomes, and associated predisposing factors of type 2 diabetic patients with isolated or combined HEs in China. Methods: We performed a retrospective analysis of 158 patients with type 2… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
4
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 27 publications
1
4
1
Order By: Relevance
“…Although speculative, the factors likely associated with the increased risk of mortality in our patients with T2DM when compared to those with T1DM are older age, the presence of comorbidities (macrovascular complications and CKD), high ICU admission rates, long lengths of stay, long times to recovery, and extended mechanical ventilation needs. Similar results were obtained from a study in Pakistan reporting higher mortality in older patients with concomitant comorbidities and T2DM (24). Interestingly, the presence of severe comorbidities has been found to be a significant independent predictor for mortality in patients with DKA (25, 27).…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…Although speculative, the factors likely associated with the increased risk of mortality in our patients with T2DM when compared to those with T1DM are older age, the presence of comorbidities (macrovascular complications and CKD), high ICU admission rates, long lengths of stay, long times to recovery, and extended mechanical ventilation needs. Similar results were obtained from a study in Pakistan reporting higher mortality in older patients with concomitant comorbidities and T2DM (24). Interestingly, the presence of severe comorbidities has been found to be a significant independent predictor for mortality in patients with DKA (25, 27).…”
Section: Discussionsupporting
confidence: 84%
“…Interestingly, all the patients with T2DM and DKA who died were classified as having moderate DKA. The overall mortality rates varied across different regions of the world, with some documenting lower rates than those in our study (23,24) and others reporting higher rates (25, 26). Although speculative, the factors likely associated with the increased risk of mortality in our patients with T2DM when compared to those with T1DM are older age, the presence of comorbidities (macrovascular complications and CKD), high ICU admission rates, long lengths of stay, long times to recovery, and extended mechanical ventilation needs.…”
Section: Discussioncontrasting
confidence: 54%
“…9,15) In HHS or mixed HHS and DKA, several studies have pointed to hyperosmolality and consequent profound hypovolemia as a major factor that influences outcomes, including altered mental status and complications such as acute kidney injury. [15][16][17][18] As observed in patients 4 and 8, who arrived in a comatose state, had significantly higher effective osmolalities than other patients did, at over 400 mOsm/kg. These results suggest that hyperosmolality should be emphasized in the diagnosis of patients with hyperglycemic crisis and highlighted as an important factor during treatment.…”
Section: Discussionmentioning
confidence: 63%
“…In the literature, we found that mixed HHS and DKA have been diagnosed during hyperglycemic crises in 14% children and 12-30% adults. [15][16][17][18] Although the diagnostic criteria for HHS and DKA are distinguishable due to differences in their pathogenesis, 1,11) the basic mechanism of the reduced action of insulin (insulin deficiency in DKA and insulin resistance in HHS) and the consequential increase in the levels of circulating counter-regulatory hormones is a pathophysiology common to both these conditions. Accordingly, clinical features frequently overlap and can lead to confusion during diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…After controlling for confounding factors, the mean adjusted LOS was 0.28 days more in the PUD group. Historically, predictors known to prolong LOS in DKA independently include age, concurrent infection, hypokalemia, lower pH on presentation, precipitating cause as infection including urinary tract infection and pneumonia, and severity of DKA based on biochemical markers including serum osmolality, anion gap apart from many others [14–18]. Studies reporting the association of quantitative HCO3${\rm{HCO}}_{3}^{-} $ on presentation found contradictory results with both positive and no association reported [14, 17].…”
Section: Discussionmentioning
confidence: 99%